Effect of Soybean Extract on sFlt-1 LEVELS in Huvecs Cultures Induced by Preeclampsia Plasma - Wiwit Indriyani; Luh Citrarasmi Dara Mestika; Tatit Nurseta; Eviana Norahmawati (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Preeclampsia is a dangerous pregnancy issue that causes hypertension at ≥20 weeks of gestation. Oxidative stress is known to play a role in the pathophysiology of preeclampsia by raising the activity of soluble fms-like tyrosine kinase 1 (sFlt-1) and causing endothelial dysfunction. As a result, antioxidants are utilized as a therapy in preeclampsia to protect the body from the impacts of free radicals. This study aims to determine the effect of soybean extract on sFlt-1 levels in HUVECs cultures exposed to preeclamptic plasma. The benefit of this study is the consideration for clinicians to provide soybean ethanol extract supplements (Glycine max) to increase the potential of antihypertensive therapy. Human umbilical vein endothelial cell cultures (HUVECs) were used in the study, which was conducted in vitro. HUVECs cultures were exposed to preeclampsia plasma and subsequently treated for 24 hours with various dosages of soybean extract. The enzyme-linked immunosorbent assay (ELISA) measured the sFlt-1 levels in each observation group. The hypothesis was tested using One-Way ANOVA analysis with SPSS version 25 software. This study found a significant difference (p <0,05) between the mean value of the positive control group and the negative control group. A significant difference was also found (p <0,05) in the mean value of sFlt-1 between the positive control group and the treatment group that was given soybean extract at doses of 17,5 ppm. Soybean extract had a significant effect on decreasing sFlt-1 levels in HUVECs cultures exposed to preeclamptic plasma. Thus, soybeans isoflavones have the potential to treat preeclampsia by reducing anti-angiogenic factors.